Penerapan Algoritma Kriptogragi Route Cipher Dengan Metode Arah Jarum Jam Pada Aplikasi Pengaman Citra Digital - Mhd Fauzi Fasha; Khairuddin Nasution; Oris Krianto Sulaiman (Deli Sains Informatika, 2021)
The problem of data or information security is an important problem in the current era of information technology. Confidentiality of data is very important to note, especially if the data contains sensitive and highly confidential information and can only be known by the parties concerned. Image is one form of information that is widely misused by irresponsible parties so that it can harm individuals, organizations, and large companies. Cryptographic technique is a method that can be used to maintain the security of the data or information. The route cipher algorithm is one of the classical cryptographic techniques that uses transposition in encryption. The strength of this algorithm is more and more complicated keys. The test results are in the form of encrypted and decrypted images, comparison of the size of the original image data with the encrypted and decrypted images, and the encryption and decryption process time. Keywords: cryptography; classic cryptography; image